Case reportRecurrent Bowen’s disease of scalp treated with high dose rate surface mold brachytherapy: a case report and review of the literature - Gandhi, Ajeet Kumar; Laviraj, Macharla Anjaneyulu; Kashyap, Lakhan; Purkait, Suvendu; Sharma, Daya Nand; Julka, Pramod Kumar; Rath, Goura Kishor (Journal of Contemporary Brachytherapy, 2014)
Our case is a 46-year-old female presenting to us with Bowen’s disease of scalp since 5 years. Patient had failed topical therapy with 5% 5-florouracil, 0.1% tacrolimus and was intolerant to topical imiquimod. At presentation, she had 15 cm × 10 cm erythematous, hyperpigmented, crusted plaque with irregular border in the superior and lateral aspect of left side of scalp with extension in to forehead. Patient was treated with computed tomography based customized surface mold high dose rate brachytherapy with Iridium-192 to a dose of 35 Gy in 10 fractions (twice daily, 6 hours apart) over 5 days. Patient tolerated the treatment well and showed regression of the lesion with mild dermatitis at the end of treatment. Though dermatitis increased at 2 weeks, at 4 weeks post treatment there was near complete resolution of the lesion with adjacent alopecia. At 8 weeks after completion of the treatment, there was complete resolution of the lesion and patient was asymptomatic. Alopecia in the adjacent area has resolved and the skin pigmentation has begun. Patient is satisfied with both the disease control and the cosmetic outcome of the procedure. Our case report demonstrates successful application of surface mold high dose rate brachytherapy in the treatment of recurrent Bowen’s disease of the scalp. Brachytherapy can play an important role in the management of recurrent malignant and premalignant diseases of the complex treatment sites like scalp and it’s non-hesitant use should be encouraged in appropriately selected patients at the earliest.